PENGARUH PEMBERDAYAAN IBU TERHADAP PENGETAHUAN PEMBERIAN ASI EKSLUSIF MELALUI PENDEKATAN MODELLING - Utami, Febi Puji; Dharmayanti, Ni Deni (Jurnal Ilmiah Kesehatan, 2022)
ABSTRACTBackground: Exclusive breastfeeding is emphasized by the World Health Organization (WHO) and the United Nations Children's Fund (UNICEF) as the optimal way to provide sufficient nutrition and protection against diseases for infants during the first six months of life. Despite its clear benefits, the prevalence of exclusive breastfeeding remains low in many countries, including Indonesia. One of the factors influencing the practice of exclusive breastfeeding is maternal knowledge about its importance and implementation methods.Methods: This study employed a quasi-experimental pre-post with a control group design. The modeling approach was utilized to empower mothers through health education. The intervention was conducted through health education using the modeling approach in the Working Area of Keramat Jati Community Health Center. The total sample size was 80 mothers, 40 in the intervention group and 40 in the control group. Data collection was done through questionnaires and observation sheets.Results: The analysis revealed significant differences in the knowledge change between the intervention and control groups after the intervention. The intervention group showed an increase in knowledge by 75.6%, while the control group showed only a 75.0% increase. Additionally, there was a significant difference in the status of infant breastfeeding between the two groups after the intervention, with 97.5% of infants in the intervention group receiving exclusive breastfeeding compared to only 70.7% in the control group. The Research Conducted in December 2021Conclusion and Recommendation: Empowering mothers through modelling approach in health education is an effective strategy in enhancing maternal knowledge about exclusive breastfeeding and influencing the status of infant breastfeeding. A holistic and sustainable approach is needed to achieve success in increasing the practice of exclusive breastfeeding.Keywords: Exclusive Breastfeeding, Maternal Knowledge, Modelling Approach, Health Education, EmpowermentÂ